Impact of pulmonary exacerbations and lung function on generic health-related quality of life in patients with cystic fibrosis. Issue 1 (December 2016) - Solem, Caitlyn; Vera-Llonch, Montserrat; Liu, Sizhu; Botteman, Marc; Castiglione, Brenda
Abstract Background The analysis aimed to examine the impact of pulmonary exacerbations (PEs) and lung function on generic measures of HRQL in patients with cystic fibrosis (CF) using trial-based data. Methods In a 48-week randomized, placebo-controlled study of ivacaftor in patients ≥12 years with CF and aG551D -CFTR mutation the relationship between PEs, PE-related hospitalizations and percent predicted forced expiratory volume in one second (ppFEV1 ) with EQ-5D measures (index and visual analog scale [VAS]) was examined in post-hoc analyses. Multivariate mixed-effects models were employed to describe the association of PEs, PE-related hospitalizations, and ppFEV1 on EQ-5D measures. Results One hundred sixty one patients (age: mean 25.5 [SD 9.5] years; baseline ppFEV1 : 63.6 [16.4]) contributed 1, 214 observations (ppFEV1 : no lung dysfunction [n = 157], mild [n = 419], moderate [n = 572], severe [n = 66]). Problems were most frequently reported on pain/discomfort, anxiety/depression, and usual activities EQ-5D items. The mean (SE) EQ-5D index nominally decreased (worsened) with worsening severity of lung dysfunction (P = 0.070): 0.931 (0.023); mild: 0.923 (0.021); moderate: 0.904 (0.018); severe: 0.870 (0.020). 146 PEs were experienced by 72 patients, including 52 PEs (35.6 %) that required hospitalization. Mean EQ-5D index and VAS scores were lowest (worst) within 1 week (before or after PE start) for PEs requiring hospitalization. Pulmonary exacerbations, PE-related hospitalizations, and ppFEV1 were significant predictors of EQ-5D index and VAS. Conclusions In a clinical study of patients with CF (≥12 years of age and aG551D -CFTR mutation), PEs, primarily those requiring hospitalization, were associated with low EQ-5D index and VAS scores. The impact of ppFEV1 was relatively smaller. Reducing PEs, in particular those requiring hospitalization, would likely improve HRQL among these patients. Trial registration ClinicalTrials.gov, NCT00909532 ; URL: clinicaltrials.gov, May 26, 2009